Freezing of gait in Parkinson's disease: Evidence of sensory rather than attentional mechanisms through muscle vibration - Pereira, Marcelo P. [UNESP]; Gobbi, Lilian T.B. [UNESP]; Almeida, Quincy J. (Elsevier, 2016)
Introduction The role of proprioceptive integration impairments as the potential mechanism underlying Freezing of gait (FOG) in Parkinson's disease (PD) is still an open debate. The effects of muscle vibration (a well-known manipulation of proprioception) could provide the answer to the debate. The aim of this study was to determine whether proprioceptive manipulation, through muscle vibration, could reduce FOG severity. Methods Sixteen PD patients who experience FOG were required to walk with small step lengths (15 cm). Cylindrical vibration devices were positioned on triceps surae tendon. Three vibration conditions were tested: No vibration (OFF), vibration on the less affected limb (LA), or on the more affected limb (MA). Additionally, we assessed the effects of applying vibration before and after FOG onset. The FOG duration and the foot used to take the next step were assessed. Results FOG significantly decreased only with vibration of LA in comparison to OFF, and when vibration was applied after FOG onset. Conclusion Our results show that muscle vibration is a promising technique to alleviate the severity of FOG. Improvements to FOG behavior were restricted to the less affected limb, suggesting that only the less damaged side of the basal ganglia may have preserved capacity to process sensory feedback. These results also suggest the likelihood of sensory deficits in FOG that cannot be explained by cognitive mechanisms, since vibration effects were only observed unilaterally.
Keywords: Freezing of gait; Muscle vibration; Parkinson's disease; Proprioception; Sensory feedback